2019
DOI: 10.1002/alr.22340
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluticasone exhalation delivery system in the management of chronic rhinosinusitis: what is the evidence?

Abstract: Background: Intranasal steroids have become part of the mainstay in the long-term management of chronic rhinosinusitis. A long-standing problem remains in efficient and easy-to-use delivery of topical corticosteroids to the nasal mucosa. Currently available means of intranasal steroid delivery include sprays, which are generally limited to treating the anterior nasal cavity, and rinses, which are not FDA-approved for this indication. The exhalation delivery system is a novel method of delivering fluticasone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In the event that this management algorithm fails, we believe that the following should be offered to the patient: consideration of additional surgery, specifically if prior surgeries did not address all surgical goals based on endoscopic and computed tomography (CT) findings and/or if appropriate postoperative treatment was not started following the initial surgery. Appropriate treatment may include leukotriene modifiers, 37 allergy immunotherapy for documented sensitivities, 38 saline irrigations, topical steroids in various forms, 39 or aspirin desensitization in interested patients. If patients were not compliant with medical therapy following their initial surgery, oral steroids followed by topical steroids, which are available via various delivery mechanisms, 39,40 should be considered prior to a revision surgery.…”
Section: Proposed Treatment Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the event that this management algorithm fails, we believe that the following should be offered to the patient: consideration of additional surgery, specifically if prior surgeries did not address all surgical goals based on endoscopic and computed tomography (CT) findings and/or if appropriate postoperative treatment was not started following the initial surgery. Appropriate treatment may include leukotriene modifiers, 37 allergy immunotherapy for documented sensitivities, 38 saline irrigations, topical steroids in various forms, 39 or aspirin desensitization in interested patients. If patients were not compliant with medical therapy following their initial surgery, oral steroids followed by topical steroids, which are available via various delivery mechanisms, 39,40 should be considered prior to a revision surgery.…”
Section: Proposed Treatment Algorithmmentioning
confidence: 99%
“…Appropriate treatment may include leukotriene modifiers, 37 allergy immunotherapy for documented sensitivities, 38 saline irrigations, topical steroids in various forms, 39 or aspirin desensitization in interested patients. If patients were not compliant with medical therapy following their initial surgery, oral steroids followed by topical steroids, which are available via various delivery mechanisms, 39,40 should be considered prior to a revision surgery. Additional surgical goals such as improved access to sinus cavities involving partial middle turbinectomy or an endoscopic modified Lothrop procedure are options for recurrent polyp patients and should be considered.…”
Section: Proposed Treatment Algorithmmentioning
confidence: 99%
“…Additionally, the design of the device allows firm sliding of the nosepiece into one nostril, sealing it firmly and hence expanding mechanically the narrow slit-shaped part of the nasal triangular valve. [183][184][185] Recent large scale studies have suggested efficacy and safety of an EDS-fluticasone formulation (EDS-FLU) in chronic rhinosinusitis patients with and without polyps, expressed as decreased Sino Nasal Outcome Test scores as well as improvement in nasal polyp score in majority (60%) of patients. Recently a 60-70% decrease of the indication for surgery has been reported following EDS-FLU use.…”
Section: Nasal Exhalation Delivery Systemsmentioning
confidence: 99%
“…Recently a 60-70% decrease of the indication for surgery has been reported following EDS-FLU use. 183,184 Xhance (fluticasone propionate), which uses this new delivery system, is currently approved for the treatment of nasal polyps in adults. It has shown promising results in adults and is currently undergoing evaluation in pediatric patients.…”
Section: Nasal Exhalation Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation